Catalytically Active Copper Phosphate–Dextran Sulfate Microparticle Coatings for Bioanalyte Sensing. (28th September 2020) - Pacchin Tomanin, Pietro; Bhangu, Sukhvir Kaur; Caruso, Frank; Cavalieri, Francesca
Abstract: Engineering reactive and functional nanostructured surfaces is important for enhancing the sensitivity and versatility of biosensors and microreactors. For example, the assembly of hybrid inorganic–organic porous microparticles on surfaces may provide a catalytic microenvironment for a wide range of reactions. Herein, the synthesis of catalytically active porous dextran sulfate–copper phosphate hybrid microparticles by a facile and rapid crystallization process in aqueous solution is reported. The sulfated polysaccharide enables control over the size and hierarchical morphology of the hybrid microparticles, as well as their assembly into stable macroporous coatings. The engineered microparticle coatings display intrinsic nonenzymatic peroxidase‐like catalytic activity when employed as a platform for the detection of hydrogen peroxide. Pairing of the microparticle coating with glucose oxidase affords a hybrid platform that is employed as a glucose sensor for monitoring physiological concentrations of a given analyte via a hybrid enzymatic/nonenzymatic cascade reaction. This work presents a strategy for the assembly of hybrid porous microparticles into enzyme‐mimicking surfaces for copper‐based catalysis and biochemical analyte sensing. Abstract : The synthesis of hybrid porous microparticles based on copper phosphate and dextran sulfate and their assembly into macroporous coatings is reported. The microparticles display highly uniform size, high stability at varied pH, controlled porosity, and catalytic activity. The coatings are employed for bioanalyte sensing and they offer high‐throughput detection and sensing of H2 O2 and glucose at physiological concentrations.